(untitled) (LACCEI, 2024)
The high contamination with heavy metals in the soils of the Mantaro Valley, Peru, and the few studies reported using organic amendments with three species led to evaluate the Pb phytoaccumulation capacity of three plant species: Taraxacum officinale (TO – the dandelion), Arabidopsis thaliana (AT), and Helianthus annuus (HA – the sunflower) on their roots and shoots. For this, these species were cultivated in pots containing agricultural soil (substrate A - 764 mg Pb/Kg) and agricultural soil + organic amendment (substrate B - 681 mg Pb/kg). Treatments were arranged in a 3 x 2 factorial random design, with three replicates. High concentrations of Pb were observed in the plants after exposure to lead-contaminated soils. For both substrates (A B), the species with the highest concentration of Pb in the shoots were TO (69.81 ± 2.58 mg/kg 56.48 ± 1.23 mg/kg) and AT (48.30 ± 2.18 mg/kg 23.78 ± 0.84 mg/kg) and with a higher concentration in the HA roots (52.96 ± 1.15 mg/kg 38.27 ± 2.76 mg/kg), Bioaccumulation factors (BCF) and translocation factors (FT) were evaluated. For substrate A, the AT species obtained a higher FT = 2.91, followed by TO (1.65). For substrate B, TO showed a value of 1.57, followed by AT (1.36). The three species demonstrated their capacity for the remediation of Pb from contaminated soils